Hubungan Regulasi Diri Dengan Status Gizi pada Remaja Akhir di Kota Denpasar - Pramitya, A.A. Istri Mira; Valentina, Tience Debora (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2013)
One of the nutritional problem in adolescent is about health which it’s also major concern in the health sector. Obesity and anemia are two things that vulnerable adolescents facing problem related to nutritional problem. Proliferation of fast food restaurant are very contradictory to the widespread phenomenon of obesity which it’s been a global epidemiology and body image distortion is concerned with anemia which it’s related with losing body weight. Nutrition fulfillment can be seen through optimal nutrition status as related to the ability of people to control their behavior, emotion and mind (drives). The purpose of this research is to explore the relationship between self-regulation with nutritional status of fulfillment. This research used quantitative methods. The subject of this research are 280 late adolescents in Denpasar. Data was gathered by using self-regulation scale (r=0,936; ?=0,273-0,625) Physical measurement with Body Mass Index (BMI) is used to measure nutritional status. Data analysis is performed by Spearman analysis. The result shows that there is correlation coefficient score (p) is 0,822. It means there is no significant relationship between self-regulation and nutritional status of late adolescents in Denpasar. Therefore, alternative hypothesis is rejected, it can caused by the theory that used in this research hasn’t been much tested in other studies, the sampling technique is less representative and there are internal and external factor which are more related with nutritional status and it will be discussed later. Key words: self-regulation, nutritional status, late adolescent.Hubungan Regulasi Diri Dengan Status Gizi pada Remaja Akhir di Kota Denpasar